Evaluating Group Member Behaviour Under Individualist and Collectivist Norms: A Cross-Cultural Comparison - Hagger, Martin; Rentzelas, P.; Koch, Severine (Sage Publications, Inc, 2014)
Research has shown that people in group contexts prefer group members who display collectivist as opposed to individualist behavior, but that preference is attenuated when the prevailing group norm prescribes individualism. The present study investigated this effect in people from a predominantly individualist or collectivist cultural background. Due to their greater sensitivity to contextual social cues, individuals from a collectivist background were expected to give more polarized evaluations of group members than individuals from an individualist background. Group member evaluations were gathered in samples from a collectivist and an individualist background, manipulating the prevailing group norm (individualist or collectivist) and the behavior of a hypothetical group member (individualist or collectivist). The previously observed attenuation effect in which people provided more positive evaluations of individualist behavior under an individualist, as opposed to a collectivist, group norm was found only in participants from a collectivist cultural background. Implications of our findings and the absence of an attenuation effect in the individualist sample are discussed.